2019
DOI: 10.7150/jca.29018
|View full text |Cite
|
Sign up to set email alerts
|

Combining Red Blood Cell Distribution Width (RDW-CV) and CEA Predict Poor Prognosis for Survival Outcomes in Colorectal Cancer

Abstract: Background : Colorectal cancer is one of the common tumors that seriously threaten human health worldwide. Serum tumor markers, including CEA and CA19-9, have become the focus of research on colorectal cancer in recent years. As one of the classic blood test results, RDW is related to the pathological features, diagnosis and prognosis of various cancers in recent studies. We hope to search the correlation between RDW and the pathological features of colorectal cancer through the following studies, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…Consistent with previous findings [ 21 , 22 ], tumor markers including CEA and vaspin can predict colorectal cancer progression. CEA is a promising tumor marker of the prognosis of colorectal cancer; a high level of CEA usually indicates a poor prognosis or survival outcome [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings [ 21 , 22 ], tumor markers including CEA and vaspin can predict colorectal cancer progression. CEA is a promising tumor marker of the prognosis of colorectal cancer; a high level of CEA usually indicates a poor prognosis or survival outcome [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous findings [ 21 , 22 ], tumor markers including CEA and vaspin can predict colorectal cancer progression. CEA is a promising tumor marker of the prognosis of colorectal cancer; a high level of CEA usually indicates a poor prognosis or survival outcome [ 21 , 22 ]. Unlike CEA, vaspin is a novel biomarker of the risk of the development and progression of certain cancers; however, it has been seldom discussed in progressive disease in colorectal cancer [ 12 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study supported the view that indicators including HGB, MCV, and MCHC were worse in colon cancers. Previous reports, including ours, had highlighted the adverse prognostic warning of CRC at excessive RDW-CV level [17,54] . Based on the previous conclusions, the results of this study again utilized and expanded the significance of high RDW-CV in peripheral blood of CRC.…”
Section: Discussionmentioning
confidence: 49%
“…Compared with the traditional pathological test of tumor lesions, peripheral blood biochemical test has the great advantages of quick and simple sample acquisition, low collection cost, minimal trauma and preoperative detection, which should be paid more attention to in research. We reported that RDW-CV (Red Cell Distribution Width-CV) combined with CEA can effectively predict the poor prognosis of CRC [17] . Similarly, it was observed that LY, HGB, MCV (Mean Corpuscular Volume), MCH (Mean Corpuscular Hemoglobin), MCHC (Mean Corpuscular Hemoglobin Concentration), PDW (Platelet Distribution Width) and some other indicators in peripheral blood of CRCs often presented comprehensive abnormalities, which aroused our strong interest.…”
Section: Ivyspringmentioning
confidence: 99%
“…On multivariate analysis, they also found RDW to be an independent prognostic factor of poor disease free survival. Li et al 22 , in a retrospective analysis of 168 patients with colo-rectal cancer, found a linear correlation between RDW levels and both 3-and 5-years disease free and overall survival. They also found that the H-RDW patients were more likely to have serosa infiltration, nodal metastases and higher TNM stages.…”
Section: Discussionmentioning
confidence: 97%